2016
DOI: 10.1007/s12560-016-9258-0
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus in Pork and Variety Meats Sold in Fresh Markets

Abstract: Swine is an economically important livestock, yet pork consumption and close contact with pigs are associated with the risk of hepatitis E virus (HEV) infection. Limited data on the prevalence of HEV in Southeast Asia have mainly examined farm animals. To investigate the potential zoonotic transmission of HEV from dietary consumption of pork and variety meats (i.e., offal or organ meats), we obtained 1090 liver, 559 pork meat, and 556 intestine samples from fresh markets in the Bangkok metropolitan area betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 74 publications
1
23
0
Order By: Relevance
“…Seroprevalence studies in Thailand further confirmed a link between dietary or occupational exposure to swine and the presence of HEV immunity . The frequency of HEV detection in pork and variety meats sold in Thai markets was similar to or lower than the prevalence found in industrialized countries …”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Seroprevalence studies in Thailand further confirmed a link between dietary or occupational exposure to swine and the presence of HEV immunity . The frequency of HEV detection in pork and variety meats sold in Thai markets was similar to or lower than the prevalence found in industrialized countries …”
mentioning
confidence: 69%
“…13,14 The frequency of HEV detection in pork and variety meats sold in Thai markets was similar to or lower than the prevalence found in industrialized countries. [15][16][17] In several countries, inadvertent HEV transmission to blood recipients was associated with blood donation from healthy donors who may have acquired zoonotic foodborne HEV infection. 18 Reports of such blood-borne HEV transmission has increased the awareness of potential risks from HEV in donated blood and blood components.…”
mentioning
confidence: 99%
“…Subtypes are no longer limited to their regions of origin, such as the discovery of both major HEV-3 groups in UK even though only G3efg has been found in indigenous pigs, 26 as well as the discovery of HEV-3f viruses in Bangkok retail pork in supermarkets. 27 All of the National University Hospital (NUH, Singapore) sequences in this study fall within subtype 3a on the phylogenetic tree. Globally, HEV-3a appears to be a well-travelled lineage, with sequences found in farmed pigs in Canada, China, Columbia, France, Indonesia, Japan, South Korea, and Philippines.…”
Section: Discussionmentioning
confidence: 89%
“…Increasing efforts in HEV surveillance has revealed a complex picture of the global circulation of HEV‐3 subtypes, with no clear regional demarcations. Subtypes are no longer limited to their regions of origin, such as the discovery of both major HEV‐3 groups in UK even though only G3efg has been found in indigenous pigs, as well as the discovery of HEV‐3f viruses in Bangkok retail pork in supermarkets …”
Section: Discussionmentioning
confidence: 99%
“…In contrast to others (Colson et al, ; Renou, Afonso, & Pavio, ), we did not find a significant association between consumption of raw meat and HEV exposure. Also in Thailand, the low prevalence of HEV RNA in pig products suggested that foodborne infections play a minor role for HEV epidemiology (Intharasongkroh et al, ).…”
Section: Discussionmentioning
confidence: 99%